1981
DOI: 10.1039/p19810001165
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxide radicals. Part 20. Formation and reactions of t-butyl p-formylphenyl nitroxide and its derivatives

Abstract: Preparation of the parent hydroxylamine of the title nitroxide and its conversion into several hydroxylamine derivatives and the corresponding nitroxides has been achieved with a view to using functionalised aryl nitroxides as spin labels. The aN values of the derived aryl nitroxides vary with the nature of their para-substituents, thus providing a potential method for identifying the site of attachment of aryl nitroxide spin labels.Reactions of a nitrone-nitroxide, derived from the title radical, with cyanois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The most extensively used method for the synthesis of linear poly(organophosphazenes) (PDCP) is a two‐step reaction sequence, in which the first step involves preparation of polydichlorophosphazene and the second one requires the replacement of the chlorine atoms by reactions with the desired nucleophiles . Initially, we have been trying to synthesize the 4‐( N ‐ tert ‐butyl‐ N ‐nitroxide)phenol as the desired nucleophile according to the literature report, Nevertheless, 4‐( N ‐ tert ‐butyl‐ N ‐nitroxide)phenol was not stable enough to be reacted with PDCP under nucleophilic conditions. A similar result was found by Yamauchi and co‐workers who reported that t ‐butyl nitroxide cyclophosphazene derivatives were too labile to be isolated .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most extensively used method for the synthesis of linear poly(organophosphazenes) (PDCP) is a two‐step reaction sequence, in which the first step involves preparation of polydichlorophosphazene and the second one requires the replacement of the chlorine atoms by reactions with the desired nucleophiles . Initially, we have been trying to synthesize the 4‐( N ‐ tert ‐butyl‐ N ‐nitroxide)phenol as the desired nucleophile according to the literature report, Nevertheless, 4‐( N ‐ tert ‐butyl‐ N ‐nitroxide)phenol was not stable enough to be reacted with PDCP under nucleophilic conditions. A similar result was found by Yamauchi and co‐workers who reported that t ‐butyl nitroxide cyclophosphazene derivatives were too labile to be isolated .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, reactive nucleophilic group carrying aromatic nitroxide radical derivatives, such as OH, NH, or SH, in the various position of aromatic ring, are instable under nucleophilic conditions both in solution and solid state due to the unpaired electron of the nitroxide radicals which can go into a self‐condensation. Thus, preparation of aromatic nitroxide radical carrying phosphazene groups via nucleophilic replacement reaction of halophosphazenes have some synthetic challenge . For example, it was reported that the reaction of a cyclotriphosphazene derivative with 4‐( N ‐ tert ‐butyl‐ N ‐nitroxide)phenoxy produced a product which was too labile to be isolated that necessity to develop different reaction routes such as postmodification of the substituted group on the phosphazene chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of N-Naphthyl-N-phenylhydroxylamines (1 ) and Nitroxides (2).-The naphthylmagnesium bromide, prepared from the corresponding bromonaphthalene (1 mol), 1,2dibromoethane (0.2 ml), and magnesium (2.2 g-atom) in a 1 : 1 mixture of benzene and tetrahydrofuran, was treated with nitrosoarene (0.45 mol) in tetrahydrofuran dropwise with stirring at -45 "C under nitrogen. The mixture was stirred for 15 min while the temperature rose to room temperature.…”
mentioning
confidence: 99%
“…N-Substituted 1,2dihydropyridines (1) are useful synthons for use in heterodiene condensation reactions and they have played a significant role in the synthesis of various alkaloids3 and bicycloheterocycles of pharmacological interest. [4][5][6][7] In some earlier studies we reported the reactions of 1,2-dihydropyridines 1 with azides,4 nitrosobenzene,5 oxyamination reagents,6 and phenylsulfonyl cyanide JV-oxide. 7 We now report the Diels-Alder reaction of 1,2-dihydropyridines 1 with nitrosocarbonyl compounds of varied dienophilicity, the electronic effect of substituents upon regiochemistry, the stereochemistry of the cycloadducts formed, and the structures of rearrangement products.…”
mentioning
confidence: 99%